1994
DOI: 10.1111/j.1468-2311.1994.tb00801.x
|View full text |Cite
|
Sign up to set email alerts
|

The Depth of Imprisonment and Prisonization: Levels of Security and Prisoners' Anticipation of Future Violence

Abstract: It was hypothesised that prison inmates assimilate into a normative prison culture comprised of violence producing admissions of future crime. Thus, 462 inmates in three dqferent custody level prisons and a control group of 126 university students were surveyed. Results show that non‐violent offenders in high custody facilities admit that they might commit violent crime, once released. However, violent offenders in a work release centre claim that violent crime is not an option for them. A conclusion arising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Moreover, does regime affect inmate attitudes about anticipated crime, too, after their release? In a word, yes, since previous research has indicated that nonviolent offenders once released were more likely to favour violent crime as an option to get what they wanted after their prison experiences than before those prison experiences, due in part to a prisonisation effect (Stevens 1994b). Reasonably, therefore, it could be argued that regime affects both inmate behaviour and recidivism; however, the longer an inmate serves in an American high-custody penitentiary probably regardless of regime, the more likely he accepts crime as an option once released (Stevens 1995b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, does regime affect inmate attitudes about anticipated crime, too, after their release? In a word, yes, since previous research has indicated that nonviolent offenders once released were more likely to favour violent crime as an option to get what they wanted after their prison experiences than before those prison experiences, due in part to a prisonisation effect (Stevens 1994b). Reasonably, therefore, it could be argued that regime affects both inmate behaviour and recidivism; however, the longer an inmate serves in an American high-custody penitentiary probably regardless of regime, the more likely he accepts crime as an option once released (Stevens 1995b).…”
Section: Resultsmentioning
confidence: 99%
“…its own regime framed within the orientations and experiences of its top managers (Bottoms, Hay and Sparks 1990;Cooke 1989;King 1991;Stevens 1994b). Thus, every prison can be understood within its own context; however, an individual prison regime sets the standard for the social relations between custodians and inmates (King 1991).…”
mentioning
confidence: 99%
“…The concept of prisonization is highly inýuential and remains in use. Its degree and nature have been explored in relation to, for example, the use of drugs (Peat and Winfree 1992 ;Thomas and Cage 1977 ;Winfree et al 1994), violence (Stevens 1994), the coercive prison environment (Thomas 1977) and people's transitions from prison to the wider community (Goodstein 1970). For example, Thomas and Cage (1977) found that drug users report higher levels of prisonization than others.…”
Section: The Indigenous Prison Culture and Prison Behaviormentioning
confidence: 99%
“…Stevens (1994) addressed the question of whether prisonization would inýuence violent behavior upon release from prison. Stevens (1994) suggests that prison experience does increase people's violent tendencies regardless of previous violent behavior and could inýuence such tendencies both inside and outside prison.…”
Section: Prison Behavior and Personal Identitiesmentioning
confidence: 99%
See 1 more Smart Citation